The table of self-accountability according to the purposes of Shariah and its impact on the integrity of an individual and society - Mohamed, Mossad Abdelhak Shaban; Elnaem, Mohamed Hassan Abdelaziz; Anuar, Muhamad Azamin; Al-Ghawil, Ismail Muhammad Umar; Saad, Muhammad Abdul Wahab Muhammad (2021)
A Muslim should practise Islam’s orders and the teachings about integrity. It is known that forgetfulness and the absence of one’s self-control and accountability may weaken the energy. A knowledgeable is self-accountable about himself and act on what is needed. For those who are self-accountable, they will have the best resting place. Lack of tables to measure integrity, lack of link between integrity and purposes of shariah or degree of benefit for an individual and society. Create a table to measure certain manifestations of integrity in a Muslim’s life. Self-monitoring and accountability table according to the purposes of shariah. The methodological questionnaire will be translated into Malay and English according to the parameters, with advanced statistics and explanations for each component. A table will be used to measure the degree of commitment by the elements, some for abandonment and others for desalination. Then, the individual performance will be measured based on four indicators. An individual’s relationship with God in term of faith (Aqidah) and worship (Ibadah) and the manifestation of the heart and the act. An individual’s relationship with oneself and the ability to know one’s weaknesses and strengths, the ability to develop world matter; religious, intellectual, scientific, and physical aspects; creativeness; and one’s specialisation. An individual’s religion. It is meant to measure the treatment with other creation and be an active member in society. The participation in religious activity. All evaluation items for this indicator will be classified into several components. What does an individual serve according to the purposes of shariah? An individual’s degree of acceptance of shariah law. Does the individual benefit another individual only or others? The evaluation will determine the level of performance in each aspect from very weak to excellent. Besides, it serves the purposes of shariah and the degree of its benefit. An individual’s ability to self-evaluate overall performance by identifying the gap for an individual or any segment helps develop future treatment and scaling-up programmes. This questionnaire can be applied at the level of an individual or group, which can be measured by the individual or with the assistance of the lecturer.